Contributing to the understanding of the dielectric breakdown channel of alumina under high voltage. Issue 13 (September 2019) - Zhang, Tao; Du, Jishi; Lei, Yangjun; Yi, Xinyu; Yin, Jie; Yu, Ping
Abstract: The breakdown channels of alumina ceramics under DC, pulse and AC signal and the effect of surface and internal pore defects on the breakdown strength of alumina ceramics have been investigated. In order to study the breakdown process of alumina ceramics, the micro computed tomography (Micro-CT) was used to non-destructively detect the breakdown channel in the experiment. Under all electrical signals, the breakdown channels of alumina ceramics had the crater as one end, and the size of the breakdown channels were positively correlated with the power of the power supply. By characterizing the breakdown channels under different voltage loading methods, it is analyzed that the breakdown process is probably from one end of the ceramic surface to the other end due to the presence of the conducting filaments. The conducting filaments theory also explains that the same amount of surface and internal defects have almost the same effect on the dielectric breakdown strength of alumina ceramics.